Secondary traumatization of psychologists working with witnesses of psychotraumatic events: a literature review - Tarasenko, Olga; Assonov, Dmytro (Psychosomatic Medicine and General Practice, 2024)
The article presents a review of previous studies focusing on the appearance of symptoms of post-traumatic stress disorder (PTSD) among psychotherapists working with individuals who have psychotraumatic experiences. The impact of psychotrauma on specialist’s mental health is determined not by a single therapeutic session frequently, but rather by the specialist’s reaction and perception of interactions with patients. Personal involvement in the patient’s traumatic experience could lead to secondary trauma and PTSD symptoms manifestation. Thus, psychotherapists who have personal experience of surviving traumatic event are more prone to secondary traumatization and PTSD working with victims due to the nature of empathy. However, high internal motivation, the adaptation ability, professional experience, strong relations with colleagues, as well as a sense of contribution importance are reducing the risk of traumatisation and lead to successful work performance. The article highlights a number of factors that both increase and decrease the likelihood of secondary trauma and PTSD, including self traumatic experience, personal motivation, work conditions, and social resources.